OVERCOMING TRAUMA IN THE BOOK OF ILLUSIONS BY PAUL AUSTER (Journal of Contemporary Philology, 2018)
The Book of Illusions, one of Paul Auster’s most famous novels, is a metaphysicalwork where most of the characters undergo a traumatic experience. Thisresearch analyses the psyche of the characters. It deals with the grieving process,specifically how the characters deal with and face their traumas, and whetherthey overcome them. Moreover, this psychoanalytic study focuses on the mainprotagonists, David Zimmer and Hector Mann, who serve as examples throughwhich the concepts of life and death are examined. The concept of trauma is approached and analysed through the work of many psychoanalysts, especially Sigmund Freud’s work and research, which helps explain how people deal with trauma. Additionally, the psychoanalysis of this research examines the conceptsof melancholia, grief, the archive, id, ego and superego, as well as the conceptsof Eros and Thanatos, which are analysed with specific examples from thenovel and other works. However, it has to be said that trauma as defined bypsychoanalysts, is not something that can be forgotten or erased, but somethingthat dwells in the psyche and helps form a person’s character, which is exactlywhat Paul Auster proves in his novel, The Book of Illusions.
Keywords: trauma; grief; melancholia; the archive; illusions